Elementary teachers' understanding of selected mathematical phrases - Almazan, Jovencia D. (1977)
This study attempted to find out elementary teachers' understanding of selected mathematical phrases expressed in words and symbols. The subjects of this study were two groups of elementary teachers. One group composed of 30 participants of the Summer Institute at the University of Sto. Tomas from April 18 to May 26, 1977. Another group were 30 elementary teachers who have not attended seminars in mathematics from the District of Digos Occidental in the Division of Davao del Sur. The instrument used was a test on Mathematical English developed and used by Prof. Josefina Fonacier in the class in Instructional Planning and Procedures for Elementary School Mathematics during the first semester of the school year 1976-1977.